Association of HLA Class I Genotypes With Severity of Coronavirus Disease-19 - Shkurnikov, Maxim; Nersisyan, Stepan; Jankevic, Tatjana; Galatenko, Alexei; Gordeev, Ivan; Vechorko, Valery; Tonevitsky, Alexander (Frontiers in Immunology, 2021)
Human leukocyte antigen (HLA) class I molecules play a crucial role in the development of a specific immune response to viral infections by presenting viral peptides at the cell surface where they will be further recognized by T cells. In the present manuscript, we explored whether HLA class I genotypes can be associated with the critical course of Coronavirus Disease-19 by searching possible connections between genotypes of deceased patients and their age at death. HLA-A, HLA-B, and HLA-C genotypes of n = 111 deceased patients with COVID-19 (Moscow, Russia) and n = 428 volunteers were identified with next-generation sequencing. Deceased patients were split into two groups according to age at the time of death: n = 26 adult patients aged below 60 and n = 85 elderly patients over 60. With the use of HLA class I genotypes, we developed a risk score (RS) which was associated with the ability to present severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) peptides by the HLA class I molecule set of an individual. The resulting RS was significantly higher in the group of deceased adults compared to elderly adults [p = 0.00348, area under the receiver operating characteristic curve (AUC ROC = 0.68)]. In particular, presence of HLA-A*01:01 allele was associated with high risk, while HLA-A*02:01 and HLA-A*03:01 mainly contributed to low risk. The analysis of patients with homozygosity strongly highlighted these results: homozygosity by HLA-A*01:01 accompanied early deaths, while only one HLA-A*02:01 homozygote died before 60 years of age. Application of the constructed RS model to an independent Spanish patients cohort (n = 45) revealed that the score was also associated with the severity of the disease. The obtained results suggest the important role of HLA class I peptide presentation in the development of a specific immune response to COVID-19.